Compressive Strength Development of Inorganic Polymeric Mortars: Effects of Water Glass and Curing: doi: 10.14456/mijet.2015.2 - WONGPA, Jakrapan; JANTATHAI, Seksan; CHEERAROT, Raungrut (Engineering Access, 2016)
We studied the development of compressive strength of inorganic polymeric mortars with and without water glass and different curing conditions. Ten different mixtures of inorganic polymer mortar were separated into two groups. Various mixtures of fly ash, sodium hydroxide solution, water glass and clean river sand were made and cured in two ways: in oven at 60oC for 48 hours and under ambient conditions. Compressive strengths were measured over 90 days. Results showed that water glass increases the compressive strength of these mortars but curing with high temperature reduced it. Moreover, mixtures with water glass cured at 60oC had the highest compressive strength (62.0 MPa) at 90 days. However, mixtures without water glass and cured under ambient condition had sufficient compressive strength for normal concrete work.